Neurons of the A5 region are required for the tachycardia evoked by electrical stimulation of the hypothalamic defence area in anaesthetized rats - López-González, Manuel Víctor; Díaz-Casares, Amelia; Peinado-Aragonés, Carlos Antonio; Lara-Muñoz, José Pablo; Barbancho-Fernández, Miguel Ángel; Dawid-Milner, Marc Stefan (The Physiological Society, 2013)
In order to assess the possible interactions between the pontine A5 region and the hypothalamic defence area (HDA), we have examined the pattern of double staining for c-Fos protein immunoreactivity (c-Fos-ir) and tyrosine hydroxylase, throughout the rostrocaudal extent of the A5 region in spontaneously breathing anaesthetized male Sprague–Dawley rats during electrical stimulation of the HDA. Activation of the HDA elicited a selective increase in c-Fos-ir with an ipsilateral predominance in catecholaminergic and non-catecholaminergic A5 somata (P < 0.001 in both cases). A second group of experiments was done to examine the importance of the A5 region in modulating the cardiorespiratory response evoked from the HDA. Cardiorespiratory changes were analysed in response to electrical stimulation of the HDA before and after ipsilateral microinjection of muscimol within the A5 region. Stimulation of the HDA evoked an inspiratory facilitatory response, consisting of an increase in respiratory rate (P < 0.001) due to a decrease in expiratory time (P < 0.01). The respiratory response was accompanied by a pressor response (P < 0.001) and tachycardia (P < 0.001). After muscimol microinjection within the A5 region, pressor and heart rate responses to HDA stimulation were reduced (P < 0.01 and P < 0.001, respectively). The respiratory response persisted unchanged. Finally, to confirm functional interactions between the HDA and the A5 region, extracellular recordings of putative A5 neurones were obtained during HDA stimulation. Seventy-five A5 cells were recorded, 35 of which were affected by the HDA (47%). These results indicate that neurones of the A5 region participate in the cardiovascular response evoked from the HDA. The possible mechanisms involved in these interactions are discussed.
Keywords: Estimulación eléctrica; Electrofisiología; A5 region; Hypothalamic defence area; Rat; Neurophysiology